The Meaning in Life and its Relationship to Moral Intelligence among High School and University Students in the Kingdom of Saudi Arabia - Al-Adasani, Lamia Abdullah Ahmed (Journal of Posthumanism, 2025)
The present study aimed to determine the relationship between the meaning in life and moral intelligence, and to reveal the differences between them according to the variables (gender/age). The study was conducted on a sample of (230) high school and university students in the Kingdom of Saudi Arabia, aged between 30 and 15 years. The Meaning in Life Scale, prepared by Steger et al. (2006), translated by the researcher, and the Moral Intelligence Scale, prepared by Yakut and Yakut (2021), translated by the researcher, were used. The researcher used the descriptive and correlational comparative approach. The results of the study revealed a positive relationship between the meaning in life and moral intelligence among the sample members, and differences between the sexes in the dimension of the presence of meaning in favour of males. There were no differences between them in the dimension of the search for meaning and in the total score of the Meaning in Life Scale. According to age, no differences were found in the dimension of the presence of meaning, while differences were found in the dimension of the search for meaning and in the total score of the Meaning in Life Scale. This was in favour of the 15-20 age group. Regarding moral intelligence, the study found no gender differences in moral intelligence across dimensions and total scores. Significant differences, however, were found according to age, in favour of the 15-20 age group, on the total score of the Moral Intelligence Scale and its dimensions, except for the Empathy and Conscience dimensions, where no significant differences were found. The study recommends the need to focus on instilling in young people the lofty meanings of life and striving to achieve them, and to develop programs and training workshops to develop moral intelligence and its skills.